Perfil proteômico, atividades biológicas e análise antigênica do veneno da serpente peruana Bothriopsis bilineata smaragdina (Loro Machaco) - Carolina Rego Rodrigues (2018)
Snake venoms are a complex mixture of substances with different actions and activities. These substances are of great interest in research and development of new drugs, due to their biotechnological potential. In addition, venom studies are important for understanding the variability, pathology and antigenicity inherent in them. According to these snake venom properties, the aim of the present study was to characterize Bothriopsis bilineata smaragdina venom, an arboreal snake from the Viperidae family, whose venom still little known. To this end, the proteomic profile of the venom and its biological and antigenic activities were analysed. The results identified a total of 122 proteins, divided into 16 different subgroups. Among them are metalloproteinases (SVMPs, 45.93%), snake C-type lectins (Snaclecs, 22.37%), snake venom serine proteinases (SVSPs, 11.11%), L-amino acid oxidases (LAAOs, 6.62%), phospholipases B (2.69%), 5nucleotidases (2.37%), phospholipases A2 (PLA2, 2.22%), phosphodiesterase (PDE, 2.20%), cystein-rich venom proteins (1.97%) and other proteins. Experimentally, the in vitro enzymatic assays showed that the venom has SVMP, SVSP, Hyaluronidase (Hyal), PLA2 and LAAO activities. The venom was also capable of causing edema, haemorrhage and lethality in vivo. Furthermore, the edema and hemorrhage activities were neutralized by the Peruvian and Brazilian antibothropic serum, indicating the presence of crossreactive antibodies in both commercial antivenoms. The results of this study contributed to a better understanding of Bothriopsis bilineata smaragdina venom and its toxins